Test Food Materials On Stretching - G.D., Shambulova; G.E., Orymbetova; K.A., Urazbayeva; G.Z., Jaishibekov; Z.T., Nurseitova; E.U., Mailybayeva; G.A., Kozhabekova; E.A., Gabrilyants (European Scientific Journal, ESJ, 2016)
In the article proposes a device for determining the structural and mechanical properties of visco-plastic food mass at a stretching, in conditions, excluding the effect of its own weight of the sample. In the study of the influence of the quality of flour, humidity, duration of aging, mechanical processing revealed that during long time aging and mechanical processing a temporary tensile strength is reduced and relative elongation is increased, that is, the dough becomes more plastic. On tensile strain we define the values at which begins the gap of the dough: the dough from flour of the premium humidity of 40% - 550 Pa and a humidity of 45% - 650 Pa; the dough from the flour of the first grade humidity of 40% - 450 Pa and a humidity of 45% - 600 Pa.